Semantic classification of substantives of the lexical-semantic field “Intellekt” in H. Hesse's novel “The Glass Bead Game” and its translation into the Russian language - L.I. Gimatova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper gives a brief overview of the study of theoretical prerequisites for the application of the field method in the study of the lexical-semantic field “Intellekt” (‘Intelligence’). In the course of the text analysis of H. Hesse’s novel “The Glass Bead Game”, the regarded field has been considered both in the context of the work itself and with account of the data obtained from the lexicographical sources. In the considered lexical-semantic field, the groups of nouns of the nuclear and peripheral zones characterized by the following five semantic features have been identified: cognitive ability by means of mind, ability to acquire knowledge using reflection, mind, mental activity, and level of intellectual capability. A number of the most vivid examples demonstrating the peculiarities of the translation of the selected substantives into the Russian language by different translators have been provided. Along with the five denoted groups of nouns, a separate group of substantives that have antonymic pairs in the nuclear and peripheral zones has been singled out. They are distinguished by the specific features that characterize the writer’s individual style. The results of the study allow to draw a conclusion about the propriety and efficiency of the field method for studying the lexical-semantic field “Intellekt”, in particular, its substantives within the work of fiction as it allows to identify both its semantically dominant and unique features.